DEBT COVENANT, FINANCIAL DISTRESS DAN PENGARUHNYA TERHADAP KONSERVATISME AKUNTANSI - Puspita, Dyah Aruning; Permata Sari, Yossi Indah; Sugiono, Djoko (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2023)
This research was conducted with the aim of knowing the effect of debt covenant and financial distress on accounting conservatism at consumer goods manufacturing company that listed at Indonesia Stock Exchange in 2019-2021. The research method use quantitative causality approach. Sampling technique used is purposive sampling and obtained sample of 34 consumers goods manufacturing company. Data processing by using Statistical Program for Social Science (SPSS) version 29. The results of this research indicate that debt covenant negative effect and significant on accounting conservatism at consumer goods manufacturing company that listed at Indonesia Stock Exchange in 2019-2021, financial distress doesn’t effect and insignificant on accounting conservatism at consumer goods manufacturing company that listed at Indonesia Stock Exchange in 2019-2021.